Lots to Plots: Building and Inventory of Vacant Land in Madison, WI - Eanes, Francis (My University, 2012)
As planners, politicians, organizations, and citizens increasingly recognize community gardens as a vital part of urban food production, efforts are necessary to systematically identify and assess urban vacant land that could be used as potential garden sites. This project uses an array of geospatial data and a site suitability index to analyze the spatial characteristics of existing community gardens in Madison, WI. This framework was applied to land in the Madison metropolitan area, resulting in an inventory of vacant land parcels. This publicly accessible database will help to move community gardening from a tolerated fringe activity to a planned and legitimized highest-and-best-use of vacant land.
Keywords: land use; urban planning; urban agriculture; community gardens; land inventory